Redes de sobrevivência nas ruas de Copacabana: uma casa com 74 cômodos e mais de 140 mil vizinhos - Gonzalez, Patricia (2016)
From the path of Zenita dos Santos Teixeira, black, born in a tribe of Tapuios Indians of Maranhão, and the stories of other individuals on the streets, ethnography, set in the streets of Copacabana, analyzes the dynamics of survival networks, focusing on how they are made, they reproduce and break. The withdrawal of Zenita the sidewalks of the neighborhood in 2012, and the compulsory reception in Abrigo Cristo Redentor, in Bonsucesso, where she lived the last years of his life under the state supervision, enabled the construction of the hypothesis that the networks on the one hand, guarantee the survival of the population called on the streets; but agents and state agencies, often articulated with other social agents who deal with this population, act in order to remove it from the public space, undoing its temporarily or permanently networks